THE FOREIGN TEACHERS OF STAVROPOL MEN'S GRAMMAR SCHOOL IN THE LATE XIX-S - EARLY- XX-S - A. N. Ptitsyn (Гуманитарные и юридические исследования)
The article examines the pedagogical activities of teachers of foreign origin in Stavropol regional men's grammar school. The author analyzes their biographies and their contribution to the development of the given educational institution.